1999
DOI: 10.1038/sj.leu.2401377
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro effects of cytokines and the hemoregulatory peptide dimer (pEEDCK)2 (pyroGlu-Glu-Asp-Cys-Lys)2 on Gα16-positive hematopoiesis

Abstract: G proteins play an important role in signal transduction from cytokine receptors to intracellular effectors via different pathways, eg involving tyrosine kinases. In our previous studies, we demonstrated that mRNA expression of the hematopoiesisspecific G protein ␣-subunit G␣16 is a sensitive marker indicating the appearance of early myeloid and lymphoid progenitors. This study was designed to investigate cytokine effects on hematopoiesis in vivo and in vitro as reflected by G␣16 expression and sensitivity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…On the other hand, p(EEDCK) 2 appears to mimic IL-6 and interleukin-11 (IL-11) and to synergize with IL-3 and SCF in stimulating the proliferation of HSC. This group also found that G ␣ 16, a G protein tyrosine kinase-like ␣ subunit, shares a sequence homology motif with p(EEDCK) 2 in its effector domain [90]. G ␣ 16 is exclusively expressed on CD34 ϩ hematopoietic cells and is markedly downregulated during differentiation.…”
Section: Endogenous Agents P-glutamic Acid-glutamic Acid-aspartic Aci...mentioning
confidence: 94%
“…On the other hand, p(EEDCK) 2 appears to mimic IL-6 and interleukin-11 (IL-11) and to synergize with IL-3 and SCF in stimulating the proliferation of HSC. This group also found that G ␣ 16, a G protein tyrosine kinase-like ␣ subunit, shares a sequence homology motif with p(EEDCK) 2 in its effector domain [90]. G ␣ 16 is exclusively expressed on CD34 ϩ hematopoietic cells and is markedly downregulated during differentiation.…”
Section: Endogenous Agents P-glutamic Acid-glutamic Acid-aspartic Aci...mentioning
confidence: 94%
“…The hemoregulatory peptide (pEEDCK)2 has the potential to replace the activity of growth factor cocktails in in vitro systems of murine hematopoiesis [13, 14] and to enhance the effect of cytokines such as IL‐3 and SCF on colony outgrowth of human CD34 + cells (stem cells [6]). Considering its activity on hematopoietic cells, the hemoregulatory peptide pEEDCK has some functional similarity to MIP‐1α that is reflected in a structural analogy involving the presence of Cys‐Cys motifs.…”
Section: Discussionmentioning
confidence: 99%
“…The hemoregulatory peptide dimer was synthesized, purified, and stored as described [6]. In short, the synthesis procedure started with the monomer [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation